2017
DOI: 10.1103/physrevc.95.014326
|View full text |Cite
|
Sign up to set email alerts
|

Combining symmetry breaking and restoration with configuration interaction: A highly accurate many-body scheme applied to the pairing Hamiltonian

Abstract: Background: Ab initio many-body methods have been developed over the past ten years to address mid-mass nuclei. In their best current level of implementation, their accuracy is of the order of a few per cent error on the ground-state correlation energy. Recently implemented variants of these methods are operating a breakthrough in the description of medium-mass open-shell nuclei at a polynomial computational cost while putting state-of-the-art models of inter-nucleon interactions to the test.Purpose: As progre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…Our geminal CI bears close resemblance to some methods which merge correlation and symmetry projection, essentially because AGP is a symmetry-projected meanfield method (AGP is equivalent to number-projected BCS). Although the two methods are distinct, geminal CI is particularly closely related to the projected configuration interaction of Ripoche et al 15 (and also to a spinprojected analog due to Tshuchimochi and Ten-no 16,17 ). A coupled-cluster generalization of our geminal CI would likewise approximate symmetry-projected coupled cluster theory.…”
Section: Discussionmentioning
confidence: 99%
“…Our geminal CI bears close resemblance to some methods which merge correlation and symmetry projection, essentially because AGP is a symmetry-projected meanfield method (AGP is equivalent to number-projected BCS). Although the two methods are distinct, geminal CI is particularly closely related to the projected configuration interaction of Ripoche et al 15 (and also to a spinprojected analog due to Tshuchimochi and Ten-no 16,17 ). A coupled-cluster generalization of our geminal CI would likewise approximate symmetry-projected coupled cluster theory.…”
Section: Discussionmentioning
confidence: 99%
“…While such models are solvable by U (1)-breaking BCS mean-field theory in the thermodynamic limit, it is important to obtain an accurate description for mediumsize systems as well 46,108,109 . In fact, it has been shown that the Richardson-Gaudin equations are equivalent to the BCS mean-field equations for thermodynamically large systems, and as such the BCS wave function and the Bethe ansatz wave function coincide in this limit 53 .…”
Section: B Perturbing the Richardson Modelmentioning
confidence: 99%
“…This is in line with the conclusions drawn in Refs. [56,57] in the context of a truncated configuration-interaction method. There were, however, some discrepancies for some states belonging to many-body Hilbert spaces with large dimensions (i.e.…”
Section: Discussionmentioning
confidence: 99%